Cancer Patients' Perceptions of the Barriers and Facilitators to Patient Participation in Symptom Management During an Episode of Admission. Issue 6 (November 2015) - Cohen, Emma; Botti, Mari
Abstract : Background: Symptoms by definition are subjective, and patients' role in their assessment and management will impact on patient outcomes; thus, symptom management is an area of acute care practice where facilitation of patient participation is vital if quality outcomes are to be achieved. Objective: This study originated from a large multimethod research program exploring patient participation in symptom management in an acute oncology setting. The purpose of this article is to explore patients' perceptions of the barriers and facilitators to participating in their symptom management during an episode of admission to an acute oncology ward and the relationships between these perceptions and patients' preference for participation. Methods: One hundred seventy-one cancer inpatients consented and completed an interview-administered questionnaire. Patients' preference for participation was measured using the Control Preference Scale. Responses to open-ended survey questions were evaluated using content analysis. Results: Ten categories were identified in the analyses of patient perceptions of the barriers and facilitators to participating in care decisions relating to their symptoms. Patients, irrespective of their Control Preference, reported multiple barriers and facilitators to participating in their symptom management. Conclusions: Patients overall perceived information as the most critical component of participation. Irrespective of patients' preference for participation, there were similarities in the barriers and facilitators to the operationalization of participation in the acute care setting reported. Implications for Practice: Understanding patient perceptions of barriers and facilitators of participating in symptom management has provided important insights into person and system factors in the acute care sector impacting quality patient symptom outcomes.